PEMETAAN NILAI PEAK GROUND ACCELERATION (PGA) DENGAN MENGGUNAKAN METODE KANAI DI KOTA BENGKULU - , YEZA FEBRIANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Microseismic survey has been carried out in Bengkulu city from 10 to 15 October 2011. This research was conducted to provide the PGA value of Bengkulu City which located in Earthquake prone area. Data acquisition were taken using DS-4A seismometer covering 21 measurement locations. The predominant period is derived from the Horizontal to Vertical Spectral Ratio (HVSR) method. Kanai method was applied to calculate the PGA value for the Earthquake event on June 4, 2000 with a moment magnitude of 7,9. From the analysis we found that Bengkulu city had PGA values from 292 gal to 852 gal. The relationship between PGA value and the geological map can be applied to give a recommendation for planning and development for government, Therefore it may help to minimize the damage and victims caused by future Earthquakes.